Application of Cloud Storage on BIM Life-Cycle Management. (22nd August 2014) - Ding, Lieyun; Xu, Xun
Because of its high information intensity, strong consistency and convenient visualization features, building information modelling (BIM) has received widespread attention in the fields of construction and project management. However, due to large amounts of information, high integration, the need for resource sharing between various departments, the long time-span of the BIM application, challenges relating to data interoperability, security and cost all slow down the adoption of BIM. This paper constructs a BIM cloud storage concept system using cloud storage, an advanced computer technology, to solve the problem of mass data processing, information security, and cost problems in the existing application of BIM to full life-cycle management. This system takes full advantage of the cloud storage technique. Achievements are reached in four areas of BIM information management, involving security and licensing management, file management, work process management and collaborative management. The system expands the time and space scales, improves the level of participation, and reduces the cost of BIM. The construction of the BIM cloud storage system is one of the most important directions of the development of BIM, which benefits the promotion and further development of BIM to better serve construction and engineering project management.